Comparison of breastfeeding practices among different social groups: Experience from North India - Khajuria, Koushal Kumar; Digra, Kishour Kumar; Pandita, Aakash (Indian Journal of Child Health, 2017)
Background: Breastfeeding is one of the most important determinants for neonatal survival, and the prevention of childhood infections. Breastfeeding practices vary among different professional and non-professional working mothers and also among different strata of society. Objectives: To assess the comparative prevalence of exclusive breastfeeding in various health professionals (Group 1), other professional women (Group 2), non-working housewives (Group 3), and laborer women (Group 4). Materials and Methods: This prospective study was conducted in the form of an interview of all above mentioned four groups of mothers using preplanned questionnaires. The mothers attending to our routine outpatient department and immunization section were randomly interviewed after taking proper informed consent. The study was conducted over a period of 1 year from January 2016 to December 2016. A total of 800 women (200 in each group) who had delivered within the past 1 year were interviewed. Results: Breastfeeding was delayed by more than 4 h in only 26% (52/200) in Group 1 (doctors/nurses/other health professionals) in comparison to 47.5%, 54.5%, and 43% of infants in Group 2, Group 3 and Group 4, respectively. Exclusive breastfeeding for ?6 months as per the WHO recommendation was not given to any of the baby among health professional group (Group 1) where it was given to only 4.5% of Group 2 mothers, 3.5% of mothers in Group 3 and around 34.5% of laborer mothers. All mothers in Group 1 started with top/formula feeds before 6 months in comparison to 95.5%, 76.5%, and 66.5% of infants in Groups 2–4, respectively. Conclusion: Despite higher rates of early initiation of breastfeeding among all the groups and particularly in health professionals, awareness of exclusive breastfeeding (EBF), the benefits of EBF was the low depicted biyearly introduction of supplementary feeding. Maternal employment was observed as a major factor for early initiation of supplementary feeding, among health and other professionals whereas hungry baby and excessive crying were major contributory factors in early initiation of supplementary feeding in urban housewives and laborer mothers. This indicates the need to further promote and create awareness about the advantages of EBF and avoid early introduction of complementary foods.